The influence of digital marketing and Islamic marketing on purchasing decisions of Muslim fashion - Aini, Laila Nur; Nafis, Abdul Wadud; Rifa’i, Khamdan (Journal of Islamic Economics Lariba, 2024)
IntroductionToday, the business world is experiencing rapid development and change every year. Many businesses have begun implementing Islamic marketing strategies to promote their products. Additionally, digital marketing has become popular among business practitioners conducting buying and selling activities. This study aims to analyze the impact of Islamic and digital marketing on purchasing decisions for Muslim fashion.ObjectivesThe objectives of this study are: 1) to analyze the influence of Islamic marketing on purchasing decisions for Muslim fashion. 2) To examine the impact of digital marketing on purchasing decisions in Muslim fashion.MethodThis study employed a quantitative approach, utilizing multiple linear regression analysis with IBM SPSS Statistics version 25. The sample size included 100 respondents. Data were collected using questionnaires distributed through Google Forms.ResultsThe study reveals the following: 1) Islamic marketing positively and significantly influences the purchasing decisions of Muslim fashion. 2) Digital marketing also positively and significantly affects purchasing decisions for Muslim fashion.ImplicationsThe findings indicate that both Islamic and digital marketing are effective strategies for influencing purchasing decisions of Muslim fashion consumers. Businesses should consider integrating these strategies to enhance market reach and customer engagement.Originality/NoveltyThis study provides new insights into the simultaneous effects of Islamic and digital marketing on consumer purchasing decisions in the context of Muslim fashion. This highlights the importance of ethical marketing practices and the use of digital platforms to reach the target audience.